2017
DOI: 10.1039/c7dt03053c
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the role of morphology on the magnetic properties of Ca2Mn3O8 materials

Abstract: CaMnO exhibits a complex layered structure comprised of MnO layers separated by Ca ions. In contrast with the more traditional triangular delafossite layered materials the MnO layers additionally exhibit an ordered vacancy, which forms a 'bow-tie' like arrangement of the Mn ions. We report a comprehensive study of the magnetic properties of a series of CaMnO materials with different morphologies. EXAFS and XANES analysis confirm no differences in either manganese environment or oxidation state between material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…24 An effective magnetic moment, m eff , was calculated at 300 K to be 6.47 m B per formula unit consistent with that expected for Mn 4+ (m calc = 6.7 m B per formula unit) in Ca 2 Mn 3 O 8 consistent with our previous study. 17 The Weiss constant, y CW , was determined to have a value of À150.5 K. The level of frustration in the material can be determined using the frustration index, f, as given by;…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 An effective magnetic moment, m eff , was calculated at 300 K to be 6.47 m B per formula unit consistent with that expected for Mn 4+ (m calc = 6.7 m B per formula unit) in Ca 2 Mn 3 O 8 consistent with our previous study. 17 The Weiss constant, y CW , was determined to have a value of À150.5 K. The level of frustration in the material can be determined using the frustration index, f, as given by;…”
Section: Resultsmentioning
confidence: 99%
“…1). 17 We demonstrated that it could be expected that Ca 2 Mn 3 O 8 materials would exhibit more complex antiferromagnetic spin order than a simple mk spin arrangement. 17 We also noted that the quality of materials produced by these methods limited any detailed magnetic studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 However, the understanding of the structure-property relationships in Ca 2 Mn 3 O 8 has largely been limited by the low crystallinity of the as synthesised materials. 29 Previously, we have demonstrated that synthetic route can have a large effect on the morphology observed. 29 Solid-state methods give large spherical particles comprised of small crystallites, sol-gel methods produce nano-sized particles and hydrothermal methods yield flake-like geometries with large surface areas.…”
Section: Introductionmentioning
confidence: 96%
“…29 Previously, we have demonstrated that synthetic route can have a large effect on the morphology observed. 29 Solid-state methods give large spherical particles comprised of small crystallites, sol-gel methods produce nano-sized particles and hydrothermal methods yield flake-like geometries with large surface areas. 29 However, all synthetic routes led to materials with low crystallinity making further analysis difficult.…”
Section: Introductionmentioning
confidence: 96%